TINJAUAN YURIDIS ANAK KORBAN TINDAK PIDANA PERSETUBUHAN OLEH ORANG TUA (PUTUSAN NO.223/PID.SUS/2020/PN.PTI) - Regina Natasya; Vientje Ratna Multiwijaya (Fakultas Hukum Universitas Trisakti, 2022)
One of the duties of parents is to protect their children. The state has assured that children's rights are protected under Law Number 17 of 2016. Problem formulation: Based on the analysis of Decision No. 223/Pid.Sus/2020/PN. Pti, is the suspect's behavior in accordance with Article 81 Paragraph 2 of Law Number 35 of 2014 addressing child protection? and what actions should be taken against parents that coerce their children into having sex (Study of Decision Number 223/Pid.Sus/2020/PN.Pti). Normative legal research technique using secondary data from library research and analytical descriptive nature. Qualitative data processing and deductive reasoning are used to reach conclusions. According to the findings of the study, the discussion, and the conclusion that the defendant's actions are improper under Article 81 Paragraph 2 of Law Number 35 of 2014 in conjunction with Law Number 17 year 2016, preferably using Article 81 Paragraph 3, the sentence imposed by law enforcement is made heavier by one-third of the criminal threat made in the study.